Characteristics of Secondary PM2.5 Under Different Photochemical Reactivity Backgrounds in the Pearl River Delta Region - Yu, Xinyang; Zhang, Yin; Liu, Ningwei; Yang, Suying (Frontiers in Environmental Science, 2022)
With the increasing control of air pollution, the levels of atmospheric particulates in the Pearl River Delta (PRD) region are gradually decreasing. However, ozone pollution has become more and more serious, and the problem of secondary aerosol pollution caused by photochemical reactions cannot be ignored. Based on the observation data of environmental and meteorological stations in the nine cities of the PRD during 2019, we investigated the variations of secondary PM2.5 (PM2.5-sec) in the PRD under different photochemical reactivity backgrounds. It was shown that the photochemical reactivities appeared more significant in the central and western areas than those in the eastern areas of the PRD and appeared more significant in inland areas than those in coastal areas. The days of moderate and high photochemical reactivities mainly appeared from August to November. PM2.5-sec concentrations were the highest in autumn, during which the regional discrepancies appeared most significantly with the highest levels in the southern areas. With the enhancement of the photochemical reactivity background, the PM2.5-sec level at each station increased significantly, which appeared significantly higher in coastal areas than in inland areas. Both PM2.5-sec and ozone concentrations showed single-peak variations, which appeared higher in the daytime than at night with the peak occurring at about 15:00. For each pollutant, the average maximum concentration appeared higher for polluted stations than for clean ones, indicating that the atmospheric oxidation background was conducive to the formation of PM2.5-sec.